Geographical and seasonal distribution of tidal body force field in the Sea of Okhotsk in the context of internal wave dynamics - Kokoulina Maria; Kurkina Oxana; Rouvinskaya Ekaterina; Kurkin Andrey (Russian Journal of Earth Sciences)
Estimates of the barotropic tidal body force for diurnal and semidiurnal tides are obtained for the Sea of Okhotsk for the summer and winter periods. It is shown that in the study area, the tidal body force for diurnal tides is significantly greater than for semidiurnal ones. The maximum values of this quantity can reach about 2-8 m2 s-2, and these values are typical for areas with a sharp bathymetric gradient. A comparison of the tidal body force for the two seasons showed noticeable differences. The features of the transformation of a barotropic tidal wave propagating in the zone of large values of the tidal body force for the K1, O1, M2 tidal constituents are demonstrated. Numerical simulations indicate that baroclinic tidal waves are effectively generated in this area, and intense short-period internal waves are likely to occur.